Relationships between Health Literacy, Self Efficacy, Social Support and Care Behavior of Caregivers of Children with Leukemia Undergoing Chemotherapy - Sutas, Saengrawee; Sanasuttipun, Wanida; Srichantaranit, Arunrat (Nursing Science Journal of Thailand, 2022)
Purpose: To examine relationships between health literacy, self-efficacy, social support and care behavior of caregivers of children with leukemia receiving chemotherapy. Design: Correlational descriptive design. Methods: The study sample included 85 caregivers of children with leukemia receiving chemotherapy aged 1-5 years attending at the pediatric hematology, oncology clinics and pediatric wards in four tertiary hospitals in Bangkok, The subjects were selected by convenience sampling, Questionnaires were used in collecting data including 1) demographic data questionnaire 2) care behavior questionnaire 3) health literacy questionnaire 4) social support questionnaire, and 5) self-efficacy questionnaire. Data analysis used were descriptive statistics and Spearman’s rank-order correlation. Main findings: Care behavior of caregivers of children with leukemia receiving chemotherapy was at high level. Health literacy and self-efficacy were significantly and positively correlated with care behavior of caregivers (r = .45, p < .01, r = .31, p < .01), respectively. However, social support was not correlated with care behavior of these caregivers (r = .13, p > .05). Conclusion and recommendations: According to the study findings, care behavior of caregivers was at a high level, and care behavior was correlated with heath literacy and self-efficacy. Therefore, healthcare team, especially physicians and nurses should enhance health literacy and self-efficacy of these caregivers. These strategies would improve care behavior of caregivers of children with leukemia receiving chemotherapy at home.